The 1965 Penrose singularity theorem. (1st June 2015) - Senovilla, José M M; Garfinkle, David
Abstract: We review the first modern singularity theorem, published by Penrose in 1965. This is the first genuine post-Einsteinian result in general relativity, where the fundamental and fruitful concept of the closed trapped surface was introduced. We include historical remarks, an appraisal of the theorem's impact, and relevant current and future work that belongs to its legacy.